TELAAH FENOMENOLOGI MERLEAU-PONTY ATAS PENGALAMAN RELIGIUS DALAM PRAKTIK KREATIF WAYANG TANTRI DI BALI - Dwipayana, A.A. Putra; Syamsuddin, Mukhtasar; Ariani, Iva (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2026)
This study aims to disclose the meaning of religious experience in the creative practice of Wayang Tantri through the phenomenological perspective of Merleau-Ponty. Employing a qualitative approach grounded in library research and hermeneutic analysis, the study demonstrates that the creativity of Wayang Tantri is not merely an aesthetic product, but an existential event unfolding through the embodiment of the dalang’s lived experience. The findings indicate that religious experience is disclosed through the dalang’s engagement with three horizons of the world: the social, the cultural-religious, and everyday experience. Religiosity does not appear as symbolic representation, but as a shared mode of inhabiting the world within the practice of performance. Through the concept of perceptual faith, religious experience is understood as the immanence of the body in its relation to the world. Accordingly, Wayang Tantri emerges as a site where artistic expression, religious experience, and existence converge within a single, interwoven horizon of experience.